Construction of PAI Learning Model Based on Knowledge Society at UIN Satu Tulungagung and IAIN Kediri, Indonesia - Tsani, Iskandar; Sufirmansyah, Sufirmansyah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This article aims to explore the construction of knowledge society-based PAI learning models in Islamic Religious Colleges (PTKI). This article was compiled based on qualitative research with a case study type. The locus of this research is UIN SATU Tulungagung and IAIN Kediri. Data collection methods used by researchers are interviews, observation, and documentation. The data analysis technique in this study is descriptive-analysis and content analysis. The flow used in interpreting this research is a qualitative data analysis technique with an interactive model proposed by Miles-Huberman, including the stages of data collection, reduction, data display, and conclusion drawing. This article concludes that the competence of lecturers in the use of IT and the various competencies of students are still the biggest obstacles faced by UIN SATU Tulungagung and IAIN Kediri in implementing knowledge society-based PAI learning. In addition, the academic culture on both campuses has not run optimally. The two campuses have the same construction of the knowledge society-based Islamic education learning model, especially in terms of enforcing academic freedom in the lecture process, routinely discussing Islamic religious education lecturers to equalize perceptions in providing inclusive PAI material within the moderation frame, and optimizing the use of IT for Islamic Islamic education lectures. What makes the difference is that UIN SATU Tulungagung implements knowledge society-based PAI learning by applying a collaborative learning model to the lecture process. Meanwhile, IAIN Kediri focuses on implementing the cooperative learning model to optimize PAI learning in the classroom.